ANALISA DAN PERANCANGAN SISTEM INFORMASI PAYROLL POLITEKNIK JAMBI BERBASIS WEB - Pusparani, Desti; Meilano, Rezagi; Tanto, Tanto (LPPM Politeknik Jambi, 2024)
Jambi Polytechnic, as the only Vocational Higher Education Institution in the Province of Jambi, requires effective and efficient payroll data management for its employees, lecturers, and staff. Currently, the existing system has expired its contract and is still in the development stage, causing difficulties for financial personnel in managing employee payroll data. Some weaknesses include the absence of features such as report summary, paycheck printing, and the use of a traditional database that is susceptible to data loss. To address these issues, this research aims to design and develop an effective and efficient payroll information system with web-based implementation at Jambi Polytechnic. Data collection methods involve observation, interviews, and documentation, utilizing the Software Development Life Cycle approach. The results include the development of a payroll information system that enhances the efficiency of payroll management, the implementation of a web-based system to improve accessibility to payroll data, and the expectation that this implementation will facilitate the performance of Jambi Polytechnic employees. Thus, the implementation of this payroll information system is expected to significantly enhance the effectiveness of payroll administration and information accessibility.